IoT based a Smart Home Automation System Design: Simulation Case - Özdoğan, Erdal; Das, Resul (My University, 2021)
Today, solutions developed with the Internet of Things have started to find more and more application areas to make human life easier. Internet of Things solutions, which include many different types of new technologies, will be very useful to use simulation tools before prototyping for the most appropriate technology selection. In this study, IoT-based smart home design applications have been developed and analyzed. In this context, 3 different scenarios have been developed for smart home automation system design in the Cisco Packet Tracer simulation environment, and the use of tools has been demonstrated with examples according to different scenarios.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği